Progression of cyclosporine A-blood levels in experimental cats receiving a high-dose treatment protocol - Rösch, Sarah; Frommeyer, Anna; Schulte Bocholt, Jenny; Grote-Koska, Denis; Brand, Korbinian; Mischke, Reinhard (Frontiers in Veterinary Science, 2024)
BackgroundCyclosporine A (CsA) is used as a steroid-sparing or alternative immunosuppressing agent in cats with various immune-mediated diseases such as immune-mediated hemolytic anemia. Daily treatment dosages of 5–20 mg/kg have been described. Interindividual variations in CsA blood levels are known to occur. To determine when steady-state conditions are reached and thus the earliest advisable time for monitoring CsA blood levels during the course of treatment, a prospective experimental study was conducted in six healthy adult Domestic Shorthair cats.Materials and methodsCats were treated with an oral dosage of 7 mg/kg CsA q 12 h for 10 days. On days 1, 2, 3, 5, 7, and 10 after the start of CsA administration (i.e., after 1, 3, 5, 9, 13, and 19 CsA administrations), EDTA blood was collected to measure the CsA level 12 h after the CsA administration (trough values) using high-performance liquid chromatography coupled to mass spectrometry (HPLC-MS/MS).ResultsStatistical analysis revealed a significant increase in mean CsA blood levels up to day 5 (2,050 ± 964.2 ng/mL [mean ± SD], 832–3,203 ng/mL [minimum–maximum]; repeated-measures ANOVA: p = 0.0021), while values on days 5 and 7 did not differ significantly from CsA concentrations on day 10. CsA concentrations showed markedly interindividual variability.ConclusionCyclosporine A blood levels reached a steady state on day 5 of high dosages of CsA q 12 h (i.e., after nine CsA administrations), indicating that this time point is suitable for monitoring blood levels in clinical patients. Results confirmed the well-known remarkable interindividual variability of CsA, indicating the need for treatment monitoring. The assessed treatment regime resulted in significantly higher mean CsA trough levels than the target range for immunosuppressive therapy (200–600 ng/mL).